Fabrication of an evanescent-field fibre optic biosensor in the development of an online bacteria detection system - Quah, Kenneth Jin Hui. (2009)
Optical fibres are fast gaining popularity as biosensors in the field of pathogen detection. This is due to their low cost, high accuracy, high efficiency and rapid detection time. This study aims to optimise the benefits of optical fibres to explore the fabrication of an online bacteria detection system. Escherichia coli (E. coli) was the bacteria of interest as its presence in water supply networks is an indicator of faecal contamination.